Analysis of the Effects of Education, Occupation Type, Household Expenditure, and Environmental Perceptions on Household Income in West Aceh Regency - Sofyana Sofyana; Affandi Affandi; Okta Rabiana Risma; Rollis Juliansyah; Yayuk Eko Wahyuningsih (The Future of Education Journal, 2026)
This study aims to analyze the influence of education, type of occupation, expenditure, and environmental perception on household income in West Aceh Regency. This research employed a quantitative approach with a sample of 100 respondents selected using purposive sampling techniques in three districts, namely Johan Pahlawan District, Meureubo District, and Kaway XVI District. Data were collected through questionnaires, interviews, and documentation. A series of linear regression analyses were used to analyze the data with the help of the IBM SPSS Statistics software. The results showed that partially, education, type of occupation, and environmental perception had a positive and significant effect on household income, while expenditure had a negative and significant effect on household income. Simultaneously, education, type of occupation, expenditure, and environmental perception had a significant effect on household income in West Aceh Regency. These findings suggest that household income can be increased through improved education, job training, and more effective household expenditure management. Therefore, to improve household welfare in West Aceh Regency, the local government must promote programs to improve education and job training and create an environment that supports community economic activity.